Reconstructing Salome: Feminism and Biblical reconstruction in Tom Robbins' "Skinny Legs and All" - Colette, Shelly Carmen (University of Ottawa (Canada), 2004)
Tom Robbins' characterization of the New Testament figure of Salome in the novel Skinny Legs and All is a medley of historical and contemporary reconstructions. Drawn from biblical and early post-biblical discourses around the Salome narrative, and bearing a strong similarity to early Roman histories of the story of Lucius Flamininus, Robbins' Salome is implicitly constructed as a romantic feminist alternative to oppressive sexual norms in Western Christian culture. Robbins' implicit intention is to provide his readers with an alternative and liberatory interpretation of Salome and the Salome narrative. Examining Robbins' reconstruction from radical feminist perspective, however, I contend that his reconstruction reinforces the same oppressive sexual norms and values he is attempting to subdue. Using the theoretical and methodological models of feminist biblical scholars Elisabeth Schussler Fiorenza and Alice Bach, I employ a critical feminist literary-biblical analysis to evaluate Robbins' characterization Salome, with an emphasis on the models of divine female sexuality he advocates through his reconstruction of her character.
Keywords: Religion, General.; Women's Studies.